2008
DOI: 10.1590/s0102-05362008000300010
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento de frutos do meloeiro sob diferentes relações fonte: dreno

Abstract: Palavras-chave:Cucumis melo, matéria seca, cultivo sem solo, carga de frutos, densidade de plantio. ABSTRACTFruit growth of melon plants submitted to different source:sink ratios An experiment was performed under protected environment from September/2004 to January/2005, to evaluate the effect of plant density and the number of fruits per plant on the growth of melon fruits cultivated in raw rice husk with recirculated nutrient solution. Three planting densities (1,7; 2,4 and 3,0 plants m -2 ) and two number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
3
3
0
3
Order By: Relevance
“…As expected, the relationship is inversely proportional which is explained by the source-sink physiology: assimilates are distributed for a greater number of entities and therefore won't fill as much, resulting also in a lower SW. Similar results were observed by Duarte, Peil, and Montezano (2008) for melons, and Zilio et al (2011) which found SP to influence SW negatively. On the other hand, PW generally increases with SW (Table 3).…”
Section: Resultssupporting
confidence: 85%
“…As expected, the relationship is inversely proportional which is explained by the source-sink physiology: assimilates are distributed for a greater number of entities and therefore won't fill as much, resulting also in a lower SW. Similar results were observed by Duarte, Peil, and Montezano (2008) for melons, and Zilio et al (2011) which found SP to influence SW negatively. On the other hand, PW generally increases with SW (Table 3).…”
Section: Resultssupporting
confidence: 85%
“…Como consequência, a partição de matéria seca para as frutas (dada pela relação matéria seca das frutas/ matéria seca total) também não foi afetada pela variação da densidade de plantio. o aumento da densidade de plantio, geralmente, reduz a expansão foliar, diminuindo a produção de matéria seca total da planta e das frutas, prejudicando, também, a partição proporcional de matéria seca e fresca para as frutas e, consequentemente, reduzindo o número de frutas colhidas e a produtividade individual das plantas, conforme verificado em hortaliças de frutos de maior porte, como pepineiro e meloeiro (PEIl; GÁlvEZ, 2002;DUARTE et al, 2008) ou em cultivares de morangueiro de alto vigor e crescimento vegetativo avantajado, quando submetidas a elevadas densidades de plantio (FREEMAn, 1981;STRASSbURGER et al, 2010). o maior sombreamento mútuo e a consequente dificuldade de penetração da radiação solar no interior do dossel reduziriam a quantidade de radiação interceptada individualmente pela planta e a taxa fotossintética, e, por conseguinte, o crescimento e a produtividade da planta sob maior pressão populacional.…”
Section: Resultsunclassified
“…In Brazil, the crop is important, providing the production of plants with high yield and with high quality of harvested fruits (Lins et al, 2013) (Duarte et al, 2008;Guimarães et al, 2008;Silva et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Thereby, the source/drain relation must be considered as a coordinate system, in which, considering plants with a limited supply, the number of drains is often reduced through loss of flowers and/or fruits. On the other hand, considering plants with limited drains, the development and/or photosynthetic activity of leaves can also be changed (Marcelis et al, 2004;Duarte et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation